Book of Abstracts of the 12th International Scientific Conference on Transformation Process in Sport "Sport Performance" Montenegrin Sports Academy - 2nd - 5th April, 2015, Podgorica - Montenegro (Montenegrin Sports Academy, 2015)
The conference is focused on current themes from all areas of sport science and sport medicine including physiology and sports medicine; social sciences & humanities; biomechanics and neuromuscular processes.